EFFECT OF REPLACING MUSTARD OILCAKE BY LINSEED OILCAKE ON GROWTH PERFORMANCE OF NILE TILAPIA (Oreochromis niloticus, Linnaeus, 1758) - Ghimire, Suraj Babu; Ranjan, Rahul (Journal of Institute of Science and Technology, 2017)
This study was done to explore the effect of replacing mustard oilcake by linseed oilcake in feed on the growth performance of Nile Tilapia (Oreochromis niloticus). Mustard oilcake (MOC) was replaced by linseed oil cake (LOC) at three different level 0%, 50% and 100% to prepare three different types of diets. Diets were prepared with about 18% analyzed crude protein content. Fingerlings were kept in three happa with three replications for each diet in completely randomized design (CRD). Fish of average weight 5.31 g were stocked in happa having size 1.5m×1.5m×1.2m. The experimental fish were fed 3% of their body weight per day, once in the morning for five months continuously. No significant difference (p>0.05) in final mean weight, final total weight, average daily weight gain (DWG), survival rate, extrapolated gross fish yield (GFY), extrapolated net fish yield (NFY) and apparent feed conversion ratio (AFCR) among different treatments were observed. Hence, linseed oilcake can be used as the substitute in the feed of tilapia, if it is locally available. Journal of Institute of Science and Technology, 2017, 22 (1): 10-16